PENGARUH CORPORATE GOVERNANCE TERHADAP PENGHINDARAN PAJAK DENGAN RISIKO PERUSAHAAN SEBAGAI VARIABEL INTERVENING - Dewi Kusuma Wardani; Maria Elvira Trifonia Dawa (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
This study aims to prove the effect of Corporate Governance on Tax Avoidance with Corporate Risk as an intervening variable. This research uses secondary data with sample data of 55 companies with a total of 275 data for 5 years that published financial statements in 2016-2020 on manufacturing companies that have been listed on the IDX. Based on the results of data analysis and discussions that have been carried out, it can be concluded that Corporate governance has a positive on Tax Avoidance. Corporate Governance has a negative effect on Corporate Risk. Corporate Risk has a negative effect on Tax Avoidance, Corporate Governance has no effect on Tax Avoidance through Corporate Risk.